Mapping of Land Surface Temperature in Relation to Rainfall in Pasuruan Regency Using Geographic Information System (GIS) - Raphael Rio Dewa Senggarang; Hendrata Wibisana (Jurnal Talenta Sipil, 2026)
This study aims to analyze the relationship between Land Surface Temperature (LST) and rainfall in Pasuruan Regency by utilizing Geographic Information System (GIS) technology. Surface temperature data were obtained from Landsat 8 Band 10 satellite imagery, which was converted into temperature in both Kelvin and Celsius, while rainfall data were collected from 20 observation stations distributed across the region.The analysis results indicate a negative correlation between land surface temperature and rainfall, particularly in high-elevation areas that exhibit lower temperatures and higher rainfall. Using the cubic polynomial model algorithm y = -3E-09x³ + 2E-05x² - 0.0272x + 43.296, the resulting correlation coefficient is 0.2762. This value falls within the interval of 0.20–0.40, which indicates a weak relationship between rainfall and land surface temperature. Rainfall, as variable X, contributes 27.62% to land surface temperature, which acts as variable Y.GIS has proven effective in visualizing the spatial distribution of temperature and rainfall data, providing valuable insights for spatial planning and climate change mitigation in tropical regions.